HAK KOMUNAL ATAS TANAH SEBAGAI HAK ATAS TANAH DESA PAKRAMAN DI BALI - Cahyadi Wiguna, Made Oka (VYAVAHARA DUTA, 2018)
The government has indeed provided legal protection and certainty to indigenous peoples regarding their ulayat lands, through a Ministerial Regulation. However, it needs to be studied more deeply about the concept of communal rights to land and Pakraman village as the subject of communal rights holders on land. Communal rights to land are conceptualized as models of land rights that have just been raised in the national land law system. The consequence is that indigenous and tribal peoples as communal rights holders are authorized to use and benefit from their communal land. Pakraman village qualifies as a subject of communal rights to land because Pakraman village in Bali is classified into the community of the community, has a system of customary government referred to as the traditional prajuru led by a customary village leader. Then Pakraman village has a legal area called the Palemahan Pakraman village. As an instrument that regulates the life and social interaction of the community, awig-awig is the customary law of the community in a Pakraman village in Bali.